INDENTIFIKASI KADAR GULA DAN KADAR NIKOTIN TEMBAKAU TALI SUMBA BARAT DAYA BERDASARKAN POSISI DAUN PADA BATANG - Dendo, Lusia; Tirtosastro, Samsuri; Tantalu, Lorine (Fakultas Pertanian, 2018)
Nicotine and sugar levels of have an important role in tobacco products. Nicotine affects the heaviness of cigarette smoke taste. A higher nicotine content will make the smoking taste heavier, in the contrary, a lower the nicotine content, will make the smoking taste lighter. Meanwhile, sugar has a role of alleviating the taste of cigarette smoke, but if it is too high it causes heat and irritation in the esophagus. This research aimed to identify the sugar and nicotine levels content of rope tobacco leaves based on the position of the leaves on the stem using factorial randomized block design (RBD). The first factor consisted of 3 levels of identification of three leaf positions, namely the upper leaf, middle leaf, and lower leaf, and the second factor consisted of 2 levels namely location one and location two and it repeated 3 times. The material studied was rope tobacco from two locations from Southwest Sumba Regency. Location I and Location II have different levels of nicotine and sugar levels. The location I had the highest nicotine content in the middle leaf position was 4.23% and the highest sugar content in the position of middle leaf was 5.12%. In location II the highest nicotine content in the upper leaf position was 6.39% and the sugar content in the upper leaf position was 3.18%. The high level of nicotine was influenced by the position of the leaves. A higher position of the leaves on the stem makes a higher nicotine level. The high level of sugar in tobacco leaves is caused by the way of cultivation which is influenced by the number of leaves left on the stem. Kadar nikotin dan kadar gula mempunyai peran yang penting dalam produk tembakau. Nikotin berpengaruh terhadap beratnya rasa isap asap rokok. Makin tinggi kadar nikotin rasa isapnya makin berat, sebaliknya tembakau yang berkadar nikotin rendah rasa isapnya makin ringan. Sedangkan gula mempunyai peran meringankan rasa asap rokok, tetapi bila terlalu tinggi menyebabkan panas dan iritasi di kerongkongan. Penelitian tentang identifikasi kadar gula dan kadar nikotin daun tembakau tali berdasarkan posisi daun pada batang menggunakan Rancangan Acak Kelompok (RAK) dalam faktorial. Faktor pertama teridiri dari 3 taraf identifikasi tiga posisi daun, yaitu daun atas, daun tengah, dan daun bawah, dan faktor kedua terdiri dari 2 taraf yaitu lokasi satu dan lokasi dua dan diulang sebanyak 3 kali. Bahan yang diteliti yaitu tembakau tali dari dua lokasi asal Kabupaten Sumba Barat Daya. Lokasi I dan Lokasi II memiliki tingkat kadar nikotin dan gula yang berbeda. Lokasi I kadar nikotin tertinggi pada posisi daun tengah yaitu 4,23% dan kadar gula tertinggi pada posisi daun tengan sebesar 5,12%. Lokasi II kadar nikotin tertinggi pada posisi daun atas yaitu 6,39% dan kadar gula pada posisi daun atas yaitu 3,18%. Tingginya kadar nikotin dipengaruhi oleh posisi daun semakin ke atas posisi daun pada batang maka kadar nikotin semakin tinggi. Tingginya kadar gula pada daun tembakau disebabkan oleh cara budidaya yang dipengaruhi oleh banyak dan sedikitnya jumlah daun yang disisakan pada batang.